Problem areas of the scholarship on China’s maritime policy in contemporary international relations studies - Yao , Zengyi (Journal of the Belarusian State University. International Relations, 2024)
This study explores the degree of the scholarly examination of China’s maritime policy within modern political science. Through this analysis, several key problem areas have been identified: the influence of China’s historical perception as a regional leader on its maritime policy, the evaluation of China’s naval capabilities, the foundational role of foreign policy principles for China’s maritime strategy, the consensus among international relations theorists that the intensification of China’s maritime policy is partly driven by US – China rivalry in the Asia – Pacific region, and the territorial disputes in the South China Sea as a primary source of regional instability. The study also proposes a new inquiry into the historical and contemporary contexts of China’s maritime policy evolution in the Asia – Pacific region, highlighting specific factors that shape the contemporary understanding of maritime security.
Keywords: China’s maritime policy; maritime security concept; international relations; military modernisation; naval forces; territorial disputes; Asia – Pacific region